2024
DOI: 10.1037/dhe0000458
|View full text |Cite
|
Sign up to set email alerts
|

“We need to see action”: An institutional case study of the Summer of Hate and Black student resistance.

Abstract: The present institutional case study explores the antecedents and aftereffects of the Unite the Right rally at the University of Virginia (UVA), a white supremacist event that occurred on August 11th and 12th in 2017. Specifically, we considered how the “Summer of Hate” informed Black undergraduate students’ sense of belonging and safety at UVA, as well as their perceptions of institutional accountability before and after the rallies. We analyzed individual interview data from 27 Black students who were newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 70 publications
(139 reference statements)
1
11
0
Order By: Relevance
“…Consistent with prior research on Black women's psychological experiences of gendered racism (Spates et al, 2020; Young, 2022) and on the connection between misogynoir and mental health concerns among Black women (Bailey, 2016; Lee & Thomas, 2022), our participants shared that their psychological wellness was at stake due to far-right misogynoir. This finding supports previous research that identified associations between far-right activity and psychological health risks among marginalized students (Albright & Hurd, 2020; Leath et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with prior research on Black women's psychological experiences of gendered racism (Spates et al, 2020; Young, 2022) and on the connection between misogynoir and mental health concerns among Black women (Bailey, 2016; Lee & Thomas, 2022), our participants shared that their psychological wellness was at stake due to far-right misogynoir. This finding supports previous research that identified associations between far-right activity and psychological health risks among marginalized students (Albright & Hurd, 2020; Leath et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Scholars should also build on our findings through studies on far-right misogynoir at larger universities not in the Northeast, as political views may vary by culture and location. For instance, Black women community organizers and college students in Virginia may have different perspectives from the participants in this study since the far-right 2017 “Unite the Right” Rally was in or close to their communities (e.g., Leath et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations